Variability of extreme precipitation in West Antarctica and its response to the Amundsen Sea Low changes - Pysarenko, L.; Pishniak, D.; Savenets, M. (Ukrainian Antarctic Journal, 2023)
Changes in precipitation extremes over West Antarctica and the Antarctic Peninsula belong to the observed consequences of current climate change. We discuss the spatio-temporal patterns of extreme precipitation and their relationships with the Amundsen Sea Low (ASL) parameters. Based on the ERA5 reanalysis data, the 95th percentile of daily precipitation totals was estimated and linked to the ASL parameters over the main glacier basins in the region. The 95th percentile of precipitation varied from 5 mm to over 40 mm over the region, showing higher values along the coastline and reaching the maximum over the west coast of the Antarctic Peninsula. The tendencies of extreme precipitation vary from –3 to 4 mm per decade and enhance the observed spatial distribution differences. On average, extreme precipitation events covered 4.7–4.9% of the basins’ area. All dependencies had a well-detected seasonality. Both total and extreme precipitation varied under the ASL fluctuations, showing significant average-to-strong correlations. The ASL shifts to the west caused a decrease in precipitation over the Amundsen Sea and an increase over the Antarctic Peninsula. The ASL deepening (lower atmospheric pressure of the system) resulted in a precipitation decrease over the Getz Ice Shelf and a precipitation increase over the western part of the Antarctic Peninsula. There are two regions with opposite responses of precipitation to the ASL changes: the western part over the Getz Ice Shelf with nearby marine areas, and the eastern part covering the Antarctic Peninsula, Pine Island glaciers, the Abbot Ice Shelf, and the Bellingshausen Sea. The obtained results are crucial for our understanding of extreme precipitation occurrences over West Antarctica in recent decades under climate change.